Terahertz Nonreciprocal Isolator Based on Magneto-Plasmon and Destructive Interference at Room Temperature - Ji, Yunyun; Fan, Fei; Tan, Zhiyu; Chang, Shengjiang (Frontiers in Physics, 2020)
A terahertz isolator is demonstrated for the THz nonreciprocal reflections in the magneto-optical microstructure composed of InSb and metasurface with a dielectric interlayer. In the Voigt magnetic field configuration, the reflectance of the p-polarization waves obliquely impinging on the InSb wafer exhibits high nonreciprocity, while the reflectance of the s-polarized wave is reciprocal. Based on the unique magneto-plasmonic modes on the InSb surface, the nonreciprocal reflection in this device can be enhanced by using the destructive interference between the direct reflection and the multiple reflections in the resonance cavity between the InSb and metasurface. After the optimization, the isolation power of the device exceeds 55 dB with the insertion loss of only −3.92 dB under a very weak magnetic field of 0.2 T at room temperature. More importantly, the introduction of the metasurface can reduce the operating frequency of the isolator from 2.434 THz to 2.136 THz. This low-loss, weak magnetic field, room temperature operating, and high isolation THz isolator shows its broad potential in THz application systems.